RyR2 and Calcium Release in Heart Failure - Benitah, Jean-Pierre; Perrier, Romain; Mercadier, Jean-Jacques; Pereira, Laetitia; Gómez, Ana M. (Frontiers in Physiology, 2021)
Heart Failure (HF) is defined as the impairment of the heart to efficiently pump enough blood to maintain the body needs, first at exercise and then also at rest. Alteration in Ca2+ handling contributes to the diminished contraction and relaxation of the failing heart. While most Ca2+ handling proteins have been shown to be altered in many models of experimental HF, in this review, we focus in the sarcoplasmic reticulum (SR) Ca2+ release channel, the type 2 ryanodine receptor (RyR2). Various modifications of this channel inducing alterations in its function have been reported. The first was the fact that is less responsive to activation by Ca2+ entry through the L-Type calcium channel, which is the functional result of an ultrastructural remodeling of the ventricular cardiomyocyte, with fewer and disorganized transverse (T) tubules. HF occurs with an elevated sympathetic tone and in an oxidant environment. In this line, RyR2 phosphorylation and oxidation has been shown in human and experimental HF. After several controversies, it is now generally accepted that phosphorylation of RyR2 at the Calmodulin Kinase II site (S2814) is involved in both the depressed contractile function and the enhanced arrhythmic susceptibility of the failing heart. Diminished expression of the FK506 binding protein, FKBP12.6, may also contribute. While these alterations have been mostly studied in left ventricle of HF with reduced ejection fraction, recent studies are looking at HF with preserved ejection fraction. Moreover, alteration in the RyR2 in HF may also contribute to supraventricular defects associated with HF such as sinus node dysfunction and atrial fibrillation.